Dry-shrinkage of sandy clay improved by ecological fibers based on experiment and DEM simulation - Hong Guo; Yuyan Lu; Wenyang Li; Fang Dang; Ya Wang; Xiaoqin Luo; Jiangtao Fu; Hong Jiang; Mingjiang Tao (Results in Engineering)
To investigate the inhibitory impact of various ecological fibers on shrinkage cracks in sandy clay, binary image processing technology was employed to quantitatively analyze water evaporation, surface crack development, evolution, and structural morphology under the influence of jute fibers and rice straw fibers. The findings indicate that ecological fibers strongly adhere to soil particles, effectively delaying soil moisture evaporation and reinforcing the soil, thus effectively suppressing shrinkage cracks in sandy clay. This suppression effect becomes more pronounced with higher fiber content. Notably, at a dosage of 0.6 %, jute fibers and rice straw fibers showed the most significant improvements: reducing crack rates by 30.6 % and 23.8 %, respectively, and average crack widths by 66.64 % and 70.86 %, respectively. The application of discrete element numerical simulations has provided further insight into the mechanical mechanism through which fibers prevent dry shrinkage cracks in sandy clay. The ecological fiber enhancement approach utilizes local materials and offers a theoretical foundation for managing dry shrinkage cracks in sandy clay filling projects.